Green Extraction of Bioactive Compounds From Marine Constituents - Raj, Bincy; Seetharam, DS; Patil, Sharangouda J (Scripta Medica, 2025)
Marine organisms house diverse bioactive compounds, making them a prime focus in marine pharmacology. This abstract explores eco-friendly extraction methods for isolating bioactive marine constituents and peptides from marine sources, underscoring their sustainability and environmental responsibility. Green extraction technologies include supercritical fluid extraction (SFE), pressurised solvent extraction (PSE) and enzyme extraction using microwaves and ultrasounds. Since there is less chemical interference, these newer, greener technologies would be safer. The extraction, isolation and characterisation of these marine constituents can lead to the identification of novel constituents from marine sources. Marine components and bioactive peptides made by marine species have a wide range of pharmacological capabilities, such as antioxidant, anti-inflammatory, antibacterial and anticancer activity. These attributes position marine-derived constituents as promising candidates for drug development and the creation of functional foods and nutraceuticals. Application of sustainable extraction methods aligns with responsible marine resource management principles; particularly important as marine ecosystems face increasing challenges from overexploitation and environmental stressors. Green extraction harmonises scientific exploration with ecological preservation within the area of marine pharmacology, promising advancements and responsible utilisation of marine resources.